Genetic diversity, preservation and use of genetic resources of Mediterranean legumes: alfalfa and medics - Prosperi J.M.; Ronfort J.; Angevain M.; Bonnin I.; Chaulet E.; Genier G.; Jenczewski E.; Olivieri I. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
The aim of the INRA (French National Institute of Agricultural Research) Montpellier - genetic resources and lucerne plant breeding laboratory is to select useful cultivars for rangelands improvement, reseeding perennial pastures or introducing forage crops in cultivated lands (grazing vineyards or rotations with cereals) in the dry and cold Mediterranean regions. These new cultivars must provide an excellent adaptation to the natural environment and farming system. Local genetic resources and especially wild ecotypes are the basis of the variability usable for these plant breeding programs. Priority is given to the genus Medicago, especially because the Mediterranean basin is the centre of diversification of this genus. Using agronomic and biomolecular tools (electrophoresis, RAPD, RFLP.), the researches focus on the study of the biodiversity of these species (distribution, ecology, ecotypic adaptation, population biology), the evolution and relationship between species or between wild and cultivated origins within Medicago sativa, relationship between the main characteristics of dry matter production, rhythms of growth, seed production and perenniality...
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)